The enhancement of the tyrrhenian coast of Calabria by endogenetic/endogenous development of local resources - Costa E.; Sturiale L.; Passarelli D.; Salamone S. (Interdependency between agriculture and urbanization: Conflicts on sustainable use of soil and water, 2001)
The study proposed here aims at putting into evidence the conflict on the use of soil between agriculture and other destinations along the Tyrrhenian Calabrian coast. Analyses provide a kaming and proposing picture reating to the lack of interaction between urban structure and agro-productive order, involving operationally the waste of space, especially the agricultural one and, as a consequence, the loss of values - potential and real - existing on coastal areas. The valorization of 'agricultural spaces' is intended here as an opportunity able to give inception to a process of integrate planning aimed at legitimizing the endogenous abilities (in the stratifications and potential uses) of agricultural private space to negotiate with various human pressures. The Thyrrhenian Calabrian coast has been bong delegitimated and depotentiated in its primary resources, so compromising the high abilities of sustainable development. An inversion of tendency is needed.
Seminar: Interdependency between Agriculture and Urbanization: Conflicts on Sustainable Use of Soil and Water, 2000/04/02-06, Tunis (Tunisia)